CBD Effects on TRPV1 Signaling Pathways in Cultured DRG Neurons - Anand U; Jones B; Korchev Y; Bloom SR; Pacchetti B; Anand P; Sodergren MH (Journal of Pain Research, 2020)
Uma Anand,1 Ben Jones,2 Yuri Korchev,3 Stephen R Bloom,2 Barbara Pacchetti,4 Praveen Anand,5 Mikael Hans Sodergren1 1Department of Surgery and Cancer, Imperial College London, Hammersmith Hospital, London W12 ONN, UK; 2Department of Metabolism, Digestion and Reproduction, Imperial College London, Hammersmith Hospital, London W12 ONN, UK; 3Nanomedicine Laboratory, BN5 Commonwealth Building, Imperial College London, Hammersmith Hospital, London W12 ONN, UK; 4EMMAC Life Sciences Ltd, London EC2A 2EW, UK; 5Peripheral Neuropathy Unit, Department of Brain Sciences, Imperial College London, Hammersmith Hospital, London W12 ONN, UKCorrespondence: Uma Anand Email u.anand@imperial.ac.ukIntroduction: Cannabidiol (CBD) is reported to produce pain relief, but the clinically relevant cellular and molecular mechanisms remain uncertain. The TRPV1 receptor integrates noxious stimuli and plays a key role in pain signaling. Hence, we conducted in vitro studies, to elucidate the efficacy and mechanisms of CBD for inhibiting neuronal hypersensitivity in cultured rat sensory neurons, following activation of TRPV1.Methods: Adult rat dorsal root ganglion (DRG) neurons were cultured and supplemented with the neurotrophic factors NGF and GDNF, in an established model of neuronal hypersensitivity. Neurons were stimulated with CBD (Adven 150, EMMAC Life Sciences) at 1, 10, 100 nMol/L and 1, 10 and 50 μMol/L, 48 h after plating. In separate experiments, DRG neurons were also stimulated with capsaicin with or without CBD (1 nMol/L to10 μMol/L), in a functional calcium imaging assay. The effects of the adenylyl cyclase activator forskolin and the calcineurin inhibitor cyclosporin were determined. We also measured forskolin-stimulated cAMP levels, without and after treatment with CBD, using a homogenous time-resolved fluorescence (HTRF) assay. The results were analysed using Mann-Whitney test.Results: DRG neurons treated with 10 and 50 μMol/L CBD showed calcium influx, but not at lower doses. Neurons treated with capsaicin demonstrated robust calcium influx, which was dose-dependently reduced in the presence of low dose CBD (IC50 = 100 nMol/L). The inhibition or desensitization by CBD was reversed in the presence of forskolin and cyclosporin. Forskolin-stimulated cAMP levels were significantly reduced in CBD treated neurons.Conclusion: CBD at low doses corresponding to plasma concentrations observed physiologically inhibits or desensitizes neuronal TRPV1 signalling by inhibiting the adenylyl cyclase – cAMP pathway, which is essential for maintaining TRPV1 phosphorylation and sensitization. CBD also facilitated calcineurin-mediated TRPV1 inhibition. These mechanisms may underlie nociceptor desensitization and the therapeutic effect of CBD in animal models and patients with acute and chronic pain.Keywords: cannabidiol, CBD, chronic pain, DRG neurons, cAMP, calcium imaging, desensitization